Exercise effects on neuropsychiatric symptoms and quality of life in mild cognitive impairment: a systematic review and meta-analysis - Chen, Liang; Kim, Sung Min (Frontiers in Neurology, 2024)
Background ： Exercise is seen as a cost-efficient option for individuals with mild cognitive impairment (MCI). While the potential benefits of exercise for improving cognitive function are recognized, its impact on neuropsychiatric symptoms (NPS) and the quality of life in individuals with MCI remains unclear.Objective ： This study aims to investigate the effects of exercise interventions on NPS, including depression, anxiety, sleep disorders, and the quality of life in individuals with MCI.Results ： Seventeen randomized controlled trials involving 1,575 participants were included. The findings indicate a small but significant positive effect of exercise on depression (SMD = -0.47, 95% CI: -0.73 to -0.21), but the quality of evidence is low. Mind-body exercises were relatively more effective in alleviating depression. No significant improvements were observed in sleep disorders (SMD = -1.27, 95% CI: -2.80 to 0.26). Exercise improved anxiety in one study but had no effect in the other, and it improved quality of life in seven studies, with two showing no effect.The findings suggest that exercise, especially mind-body exercises, can improve depression in individuals with MCI. However, the effect of exercise on anxiety, sleep disorders, and quality of life is still uncertain, necessitating additional research. These findings underscore the significance of integrating customized exercise programs in managing MCI to boost quality of life and mitigate NPS.Research shows that 35-85% of individuals with MCI have at least one NPS, with depression having the highest reported NPS prevalence rate (83% for aMCI and 73% for naMCI) (Martin and Velayudhan, 2020). Anxiety and sleep disorders are also common in MCI, with prevalence rates of over 70% and 39% respectively (Rozzini et al., 2007). In addition, negative psychological states significantly impact the quality of life in individuals with MCI (